2021
DOI: 10.1016/j.ajem.2020.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of hydroxychloroquine in 152 outpatients with confirmed COVID-19: A pilot observational study

Abstract: We investigated the efficacy and safety of hydroxychloroquine for empirical treatment of outpatients with confirmed COVID-19. Methods: In this prospective, single-center study, we enrolled ambulatory outpatients with COVID-19 confirmed by a molecular method who received hydroxychloroquine. The patients were divided into low-and moderaterisk groups based on the Tisdale risk score for drug-associated QT prolongation, and the QT interval was corrected for heart rate using the Bazett formula (QTc). The QTc interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…Similar results have been reported in other non-randomized studies (Sulaiman et al 2020;Mohana et al 2021;Sogut et al 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Similar results have been reported in other non-randomized studies (Sulaiman et al 2020;Mohana et al 2021;Sogut et al 2021).…”
Section: Discussionsupporting
confidence: 91%
“…The number of patients with peak QTc > 500 ms were not significantly different 25 . A prospective study confirmed that HCQ was harmless for COVID‐19 patients and did not associate with a risk of arrhythmia induced by QTc prolongation 32 …”
Section: Discussionmentioning
confidence: 82%
“… 25 A prospective study confirmed that HCQ was harmless for COVID‐19 patients and did not associate with a risk of arrhythmia induced by QTc prolongation. 32 …”
Section: Discussionmentioning
confidence: 99%
“…In observed observational studies, the outcomes below have been reported. In these studies, it was reported that a percentage of participants received from HCQ had prolonged QTc intervals (Ip et al, 2021;Sogut et al, 2021;Fteiha et al, 2020). In the study by Sogut et al (2021), 91.4% of the participants showed significant improvement, however 13 had adverse events (Sogut et al, 2021).…”
Section: Average Of 65 Yearsmentioning
confidence: 98%
“…In these studies, it was reported that a percentage of participants received from HCQ had prolonged QTc intervals (Ip et al, 2021;Sogut et al, 2021;Fteiha et al, 2020). In the study by Sogut et al (2021), 91.4% of the participants showed significant improvement, however 13 had adverse events (Sogut et al, 2021). However, the results of these studies were very limited given the small number of participants.…”
Section: Average Of 65 Yearsmentioning
confidence: 99%